Best approximation of Hartley-Bessel multiplier operators on weighted Sobolev spaces - Ahmed Chana; Abdellatif Akhlidj (Journal of Numerical Analysis and Approximation Theory)
The main goal of this paper is to introduce the Hartley-Bessel \(L^2_α\)-multiplier operators and to give for them some new results as Plancherel’s, Calderon’s reproducing formulas and Heisenberg’s, Donoho-Stark’s uncertainty principles. Next, using the theory of reproducing kernels we give best approximation and an integral representation of the extremal functions related to these operators on weighted Sobolev spaces.